Pendidikan Madrasah dalam New Normal - Ahmad Taufik; Dedi Heriansah (Edification Journal : Pendidikan Agama Islam, 2021)
Islamic education has an important history. the development and growth of Islamic education exists naturally as Islam develops. In general, education is an important thing in human life. Because basically education, when viewed from its function, is to want to form human beings, who have noble character and good character, for the sake of achieving a happy life, both in this world and in the hereafter. In this case, the role of Islamic education institutions, one of which is that madrasas must be able to keep up with all of these things and be able to direct their students so that in their output they can compete with other countries and not lose in terms of knowledge and technology, without leaving the soul and characteristics of Islam in his life.